Gestazione per altri (ed altre). Spunti per un dibattito in (una) prospettiva femminista (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The essay tries to offer a feminist view of the ‘surrogacy’. It would suggest some relevant points by which to analyse the possible vantages and disadvantages of that practice for women, clarifying if it could be intended as a practice of emancipation from patriarchy, a mean of women empowerment, or not. Which role for the law in a global market?
Keywords: feminism; surrogacy; patriarchy; genetic; propriety.